1999
DOI: 10.7863/jum.1999.18.4.265
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of aneuploidy with a cardiac intraventricular echogenic focus in an at-risk patient population.

Abstract: The objective of this study was to determine the relative risk for aneuploidy in the presence of a cardiac intraventricular echogenic focus in a patient population at high risk for aneuploidy. A retrospective cohort study was conducted on patients referred to a fetal diagnostic center who were undergoing amniocentesis. Records and second trimester sonograms were reviewed. Approximately 5100 comprehensive prenatal sonograms were obtained over a 2 year study period. Karyotyping by amniocentesis was done in 2412 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 15 publications
2
33
0
Order By: Relevance
“…Since the inclusion of the four-chamber view in the standard anatomical ultrasound evaluation, the finding of fetal cardiac echogenic foci has understandably increased significantly. Most studies have included fetuses at risk for chromosomal abnormalities and mothers with risk factors such as advanced maternal age or abnormal serum screening [2,5,[8][9][10]. Studies on low-risk populations have reached the conclusion that the finding of echogenic foci is most likely a variant of the normal if detected as an isolated finding [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the inclusion of the four-chamber view in the standard anatomical ultrasound evaluation, the finding of fetal cardiac echogenic foci has understandably increased significantly. Most studies have included fetuses at risk for chromosomal abnormalities and mothers with risk factors such as advanced maternal age or abnormal serum screening [2,5,[8][9][10]. Studies on low-risk populations have reached the conclusion that the finding of echogenic foci is most likely a variant of the normal if detected as an isolated finding [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…The source of the echogenic foci has been speculated to be calcifications within the papillary muscles of the fetal heart [1], a finding seen more frequently on autopsy of chromosomally abnormal than of normal fetuses [5]. The reported incidence of echogenic foci within the left ventricle of the fetal heart ranges from 0.5 to 20% [1][2][3]6], some reporting it to be a benign finding [1][2][3][4] and some showing an association with chromosomal abnormalities (trisomies 13, 18, and 21) [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Wax and Philput 123 reported that aneuploidy was more common when echogenic foci involved both ventricles compared with either ventricle alone. Vibhakar et al 117 found that of 15 fetuses with multiple EIF, 10 (67%) had abnormal karyotypes, and only 2 of those had other sonographically detected abnormalities besides EIF. More recently, Wax and colleagues 125 correlated an increased risk of aneuploidy with the conspicuity of EIF.…”
Section: Echogenic Intracardiac Foci (Or Papillary Muscle Calcification)mentioning
confidence: 99%
“…Echogenic Intracardiac Focus DeVore 71 Vergani 94 Gray 79 Nicolaides 88 Boyd 63 Verdin 93 Manning 86 Nyberg 40 Vibhakar 95 Bromley 42 Bromley 64 Data shown for all studies that examined the ultrasonographic markers as screening tests for Down syndrome. One summary estimate is included for each study.…”
Section: Deren 70mentioning
confidence: 99%